Hubungan Antara Gaya Hidup Hedonis dan Perilaku Konsumtif pada Mahasiswa - Hasnidar Thamrin Thamrin; Adnan Achiruddin Saleh (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
This research is a correlation study which aims to determine whether there is a relationship between the hedonic lifestyle and the consumptive behavior of Parepare students. The research method uses a quantitative approach. The sample in this study were 31 students in Parepare aged 19-20 years. The data collection technique was carried out by distributing a hedonic lifestyle scale and an online consumptive behavior scale using a Likert scale. Data analysis was performed using the Pearson correlation technique with the help of SPSS version 22. The results of the study showed a relationship between the hedonic lifestyle and the consumptive behavior of Parepare students. When viewed from Pearson Correlations 0.671 with a Sig. (2-tailed) 0.000, which means less than 0.05, so it can be said that there is a significant correlation between the hedonic lifestyle and consumptive behavior. Hedonic lifestyle and consumptive behavior are related to each other, if the hedonic lifestyle is higher, the higher the consumptive behavior. So, when you have a hedonic lifestyle, you will behave consumptively.